THE RELATIONSHIP BETWEEN THE DURATION OF 3 MONTHS OF KB CONTRACEPTIVE USE AND BLOOD PRESSURE IN LONG-TERM ACCEPTORS IN THE TAMIANG LAYANG COMMUNITY HEALTH CENTER UPTD AREA - Soni Ariani Candra; Anik Sri Purwanti (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2026)
This study explores the relationship between the duration of 3-month contraceptive use (KB) and blood pressure in long-term users at the Tamiang Layang Community Health Center UPTD. Contraceptive use, especially hormonal methods like the 3-month injectable, is crucial for family planning but may impact health parameters such as blood pressure. Long-term use of such contraceptives can lead to hypertension if not properly monitored, posing health risks. Previous studies have highlighted variations in blood pressure responses among users, suggesting that factors like maternal age, lifestyle, and pre-existing conditions may influence these outcomes. This research used a cross-sectional observational design with 30 long-term KB acceptors. Data on contraceptive use duration and blood pressure were collected through interviews and clinical assessments. The study found that while most participants had normal blood pressure, a smaller proportion showed elevated levels. The Wilcoxon signed-rank test yielded a significant p-value of 0.000, indicating a meaningful relationship between contraceptive use duration and blood pressure. The study concludes that health workers should monitor blood pressure regularly in long-term contraceptive users and provide counseling to mitigate potential risks. Regular check-ups and lifestyle guidance are essential for maintaining cardiovascular health among users.